Logika i praktyka. Z badań nad życiem Kazimierza Ajdukiewicza - Gan-Krzywoszyńska, Katarzyna; Leśniewski, Piotr (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The paper introduces unique excerpts from Kazimierz Ajdukiewicz’s correspondence, which illustrate the reasons why his stance on sustaining courses in logic as mandatory classes was so uncompromising. Authors also briefly sketch their own position on this matter. Additionally, a model partition of philosophical issues with reference to the Stoic division is described.